المنشآت العمومية الرومانية في بلاد المغرب القديم (El-Wahat Journal for Research and Studies, 2025)
The Roman cities that were established in the countries of the ancient Maghreb are consideredmodels of the methods of ancient architectural arts, the effects of whichstillexist to thisday. andWhichisknown for itsurbanfacilities of a pure Roman character, and whichalsodiffersfrom the local urban style.   Key words:Facilities, public,Roman ,Countries Maghreb, Ancient.